Co-infection of Mycoplasma gallisepticum and Escherichia coli Triggers Inflammatory Injury Involving the IL-17 Signaling Pathway - Wu, Zhiyong; Ding, Liangjun; Bao, Jiaxin; Liu, Yuhao; Zhang, Qiaomei; Wang, Jian; Li, Rui; Ishfaq, Muhammad; Li, Jichang (Frontiers in Microbiology, 2019)
Mycoplasma gallisepticum (MG) and Escherichia coli (E.coli) are well known respiratory disease inducing pathogens. Previous studies reported that co-infection by MG and E.coli causes significant economic losses in the poultry industry. In order to assess the respiratory toxicity of co-infection in chicken lung, we established a co-infection model to investigate the changes in inflammatory cytokines, lung tissue structure and transcriptome profiles of chicken lung. The results showed that co-infection caused a wider range of immune damage and more severe tissue lesions than single pathogen infection. Differentially expressed genes (DEGs) analysis indicated that 3,115/1,498/1,075 genes were significantly expressed among the three infection groups respectively. Gene ontology and KEGG analysis showed genes enriched in response to immune response, cytokine-cytokine receptor interaction and inflammation-related signaling pathway. Among these pathways, IL-17 signaling was found to be significantly enriched only in co-infection. The expression of IL-17C, CIKS, TRAF6, NFκB, C/EBPβ and inflammatory chemokines were significantly up-regulated in response to co-infection. Taken together, we concluded that co-infection increased the expression of inflammatory chemokines in lungs through IL-17 signaling, leading to cilia loss and excessive mucus secretion. These results provide new insights for co-infection and reveal target proteins for drug therapy.